A phenomenological and metacognitive pedagogy - Pietro Sacchelli (Pensa MultiMedia, 2022)
The article analyzes the differences extensively studied by sociolinguistics and psychology between inner and social language as well as the role played in learning by endophasic or subvocal thinking. The scientific research in the last decades has shown that the knowledge processes can be traced back to both the logical-propositional principles and the mental images (thought images), particularly investigated by Shepard and Kosslyn. The primary functions of thought, as defined by cognitivism, are however incomplete and not very usable by teachers in their classroom work if they are not accompanied by a metacognitive and phenomenological vision. In other words, in teaching, cognitivist theories are functional if enriched by approaches of the theory of mind such as the enhancement of learning styles. Only an integrated didactic proposal could give a fresh impetus to the Italian school system and help it move towards objectives that are still far from being achieved, such as personalization, school inclusion and the enhancement of differences.